The Effect of Ginseng Extract on Serum Interleukin-6 Levels in Patients with Community-Acquired Pneumonia - Fachrurrodji Fachrurrodji; B. Rina A. Sidharta; Dian Ariningrum; JB. Suparyatmo; MI. Diah Pramudianti (Indonesian Association of Clinical Pathologist and Medical laboratory, 2022)
Community-Acquired Pneumonia (CAP) is the most common cause of death and illness in the world. Increased IL-6 can be used as an early indicator of infection or inflammation. Ginseng is a popular herbal medicine. The anti-inflammatory effect of Ginseng is mediated by its ability to inhibit Nuclear Factor Kappa Beta (NF-kB), a proinflammatory regulator to initiate the synthesis of cytokines TNF-Î±, IL-1Î², IL-6, and IL-8. Clinical trial research, quasi-experimental design with a pretest-posttest approach was carried out on 26 community pneumonia patients who were hospitalized at Dr. Moewardi Hospital, Surakarta from October 2020 to January 2021 using purposive sampling. The independent variable was Ginseng extract (GinsanaR) at a dose of 2x100 mg and the dependent variable was serum IL-6 levels. Serum IL-6 levels were measured using the Sandwich Enzyme-Linked Immunoabsorbent Assay (ELISA) method. Mean IL-6 levels in the control group on day 0, day 3, and day 14 were 232,89+156,61 pg/mL, 113,46±83.30 pg/mL and 66.18±66.02 pg/mL, respectively (p=<0.001). Mean IL-6 levels in the treatment group on day 0, day 3, and day 14 were 519,55±609,19 pg/mL, 205.41±329.17 pg/mL and 133,59±291,68 pg/mL, respectively (p=<0.001). Delta IL-6 levels in the control group and the treatment group on day 3 compared to day 0, the mean of the IL-6 control group -119,42±111,70 pg/mL, the mean for the IL-6 treatment group -314,14±532,16 pg/mL; On day 14 compared to day 0, the mean of the IL-6 control group was -166,70±135,54 pg/mL, the mean of the IL-6 treatment group was -385,96±547,10 pg/mL; On day 14 compared to day 3, the mean IL-6 control group was -47.28±47.47, the mean IL-6 control group was -71.82±58.16. The post hoc test (Wilcoxon) obtained a p-value < 0.05, suggesting that Ginseng extract has a significant effect on reducing serum IL-6 serum levels in community pneumonia patients.